2013
DOI: 10.1021/jp401767c
|View full text |Cite
|
Sign up to set email alerts
|

Driving Force for Crystallization of Anionic Lipid Membranes Revealed by Atomistic Simulations

Abstract: Crystalline vesicles are promising nanomaterials due to their mechanical stability in various environments. To control their fabrication, it is essential to understand the effects of different experimental conditions on crystallization. Here we perform atomistic molecular dynamics simulations of anionic lipid membranes of 1,2-dilauroyl-sn-glycero-3-phosphol-L-serine. In the presence of Na(+) monovalent counterions, we access the phase transition from the liquid-like disordered liquid-crystalline phase to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…The observed irregular faceted shapes arise only in hexagonal crystalline lattices, where crystalline domains are separated by soft interfaces that bend to release stress. Since ionic crystalline domains also arise upon the adsorption of multivalent ions on lipids, 27 our results suggest that spherical-to-faceted reversible transitions can be induced in cationic lipid vesicles by adding (or chelating) metallic multivalent ions.…”
Section: A(b) Imentioning
confidence: 66%
“…The observed irregular faceted shapes arise only in hexagonal crystalline lattices, where crystalline domains are separated by soft interfaces that bend to release stress. Since ionic crystalline domains also arise upon the adsorption of multivalent ions on lipids, 27 our results suggest that spherical-to-faceted reversible transitions can be induced in cationic lipid vesicles by adding (or chelating) metallic multivalent ions.…”
Section: A(b) Imentioning
confidence: 66%
“…The simulation results show that the amphiphiles pack in hexagonal lattice in both cases, with a reduction in the area per molecule from 0.207 nm 2 (C 14 ) to 0.200 nm 2 (C 16 ). The simulations also reveal an enhancement in the van der Waals interactions from -27 k B T to -33 k B T per hydrocarbon tail when the tail length n increases from 14 to 16, which suggests a gain of ∼2 k B T per hydrocarbon atom in the crystalline membrane structure (17). The hydration of lipid bilayers has been studied previously by MD simulations in systems with charged groups such as dimyristoylphosphatidylcholine (DMPC) lipid bilayers (37), which showed that the average number of hydrogen bonds per lipid oxygen atom varies depending on its position within the lipid.…”
Section: Resultsmentioning
confidence: 82%
“…The presence of polar and hydrophobic groups in their wall envelopes and the fact that they survive at low pH values and disintegrate or become spherical (the shape of closed liquid membranes) when divalent metal ions are chelated (11,13) suggest that their crystallization is triggered by electrostatic interactions. Divalent ion-induced crystallization of anionic membranes has been recently studied (16,17), but crystallization changes induced by pH variations in bilayers are unknown. Here, we study pH effects in crystalline membranes of coassembled amphiphiles with carboxylate and dilysine headgroups, whose pK a values are about 5.5 (18) and 10 (19), respectively.…”
mentioning
confidence: 99%
“…The biologically most relevant phases of lipid bilayers are the liquid crystal (LC) and the gel (GL) phases [9,10]. In the presence of short-chain aliphatic alcohols, a third type of phase can appear, the interdigitated (ID) phase [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the Lˇ form of the GL phase, the tails are tilted with respect to the bilayer normal [9,10]. In the Lˇform, the tails are oriented perpendicularly to the bilayer midplane [16].…”
Section: Introductionmentioning
confidence: 99%